Effect of Dietary Incorporation of Chili (Capsicum annuum) Leaf Powder on Production Performance and Egg Quality Parameters of Rhode Island Red Laying Hens - Abhilasha; Mondal, B. C.; Kumar, Ripusudan; Palod, Jyoti; Huozha, Ruokuobeinuo; Kumar, Anil; Prasad, Srishtipriya; Ranwa, Suman (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present experiment was planned to ascertain the effect of dietary incorporation of chili (Capsicum annuum) leaf powder on production performance and egg quality parameters of Rhode Island Red laying hens of 28 weeks of age for a period of 12 weeks. Hens were individually weighed and then randomly assigned into four treatment groups with three replicates of 6 birds each viz., T1: (control, containing basal diet); T2: Incorporation of 0.5% chili leaf powder in basal diet; T3: Incorporation of 1.5% chili leaf powder in basal diet; T4: Incorporation of 2.5% chili leaf powder in basal diet. The results indicated that egg production and feed conversion ratio were not significantly affected. However, overall average feed intake significantly (P<0.05) reduced in hens supplemented with 2.5% chili leaf powder. Egg quality parameters viz., egg weight, shape index, shell weight percentage and shell thickness of eggs, egg albumen quality such as albumen height, albumen weight and Haugh unit were statistically similar among all the groups. The egg yolk quality parameters including yolk weight, yolk percentage, yolk index, yolk cholesterol and yolk triglycerides did not differ significantly among different treatment groups, however, egg yolk colour was significantly (P<0.05) improved in T4 group, compared to T1 group. While, egg yolk colour in treatment groups T1, T2 and T3 showed no significant difference. To conclude, supplementation of chilli leaf powder @ 2.5% can be used to improve egg yolk colour.